Project Work: An Experiential Journey Towards the Conquer of Self-Confidence (2016)
ABSTRACT: This paper presents and Action Research study on the impact of the implementation of a project work in students’ self-confidence while developing public speaking performances. The study was conducted in a public institution in Itagüí with 35 eighth graders. Data was collected through research journals, focus groups interviews to students, and a semi- structured interview to the Cooperating Teacher. Data analysis showed that while students were developing each of the four project work didactic units, they were able to improve some aspects related with self-confidence in public speaking activities such as power relations, language anxiety, presentation skills, and social construction. Furthermore, students’ work in their own themes for their projects allowed them to support each other, and to share more experiences.